2016
DOI: 10.1007/s00192-016-3152-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of pelvic floor dysfunction in an adult cystic fibrosis population: a questionnaire survey

Abstract: PF dysfunction affects the adult CF population, with PF symptoms limiting the ability of up to one in three patients to participate in physiotherapy management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…In these men, sexual dysfunction and difficulty in establishing intimate relationships have been reported 114 . However, these concerns were more often associated with disease-related problems than obstructive azoospermia status 114,115 . In general, sexual function is not affected until cystic fibrosis becomes severe enough to interfere with the patient's general health 116,117 .…”
Section: Azoospermia and Sexual Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these men, sexual dysfunction and difficulty in establishing intimate relationships have been reported 114 . However, these concerns were more often associated with disease-related problems than obstructive azoospermia status 114,115 . In general, sexual function is not affected until cystic fibrosis becomes severe enough to interfere with the patient's general health 116,117 .…”
Section: Azoospermia and Sexual Dysfunctionmentioning
confidence: 99%
“…Untreated men with congenital hypogonadotropic hypogonadism have infertility and reduced sexual activity 113 . Finally, men with obstructive azoospermia owing to cystic fibrosis can develop sexual dysfunction 114 associated with the severity of the disease and disease-related problems [114][115][116][117] .…”
Section: Azoospermia and Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…87 Although prevalence of reported sexual dysfunction in people with CF varies by age (and thus likely by disease severity and concomitant comorbidities) rates as high as 43% in women and 65% in men are reported. 61 , 88 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, coughing-induced fecal incontinence may discourage some cystic fibrosis patients from coughing in order to clear their airway. In a recent study [3] of 60 adults with cystic fibrosis, reported incontinence for flatus was 43% in women and 25% in men, incontinence for diarrhea was 21% in women and 6% in men, and incontinence for stools of normal consistency was 11% in women and 3% in men. No overall estimate of the prevalence of fecal incontinence was included in that study, and no risk factors were identified.…”
mentioning
confidence: 97%